The sublimity of document cinema as diorama : (avant-doc 2) - MacDonald, Scott 1942- (Oxford University Press, 2019)
"The Sublimity of Document: Cinema as Diorama is a collection of in-depth, substantive interviews with filmmakers devoted to documenting places and events that most of us never get to see--often, places and events that have considerable influence on our lives. The 27 interviews offer an engaging panorama of the recent history and geography of cinema devoted to documenting the world around us, as well as an in-depth look at the challenges and accomplishments of filmmakers willing to go anywhere on the planet (or on the internet!) to document what they believe we need to see"--
Keywords: Dokumentarfilmer; Dokumentarfilmerin; Dokumentarfilm; Documentary films / History and criticism; Experimental films / History and criticism; Motion picture producers and directors / Interviews; Documentary films; Experimental films; Motion picture producers and directors; Criticism, interpretation, etc; Interviews; Interview